Characteristics of Sediment Transport After Morphological Changes at Palu Estuary, Sulawesi, Indonesia as The Impact of 2018 Tsunami - Herman, Rudi; Tanga, Arody; Tunas, I. Gede; Ishak, Muh Galib; Madman, Ardee (International Journal of Integrated Engineering, 2022)
The tsunami triggered by the 2018 Palu Earthquake has not only caused the collapse of public infrastructure, but also damaged beaches along Palu Bay. Based on direct investigation along the beaches, the coastlines have shifted inland up to 30 meters. This shoreline change was caused by the attack of the tsunami waves at high speed followed by massive abrasion. Another impact of the wave attack is a change in the morphology of the beach bed, including in the Palu Estuary. This study aims to investigate the impact of changes in bed morphology around the Palu Estuary as a result of the tsunami attack on transport sediment characteristics, as one of the determinants of bed morphology. Quantitative analysis was carried out by numerical simulation based on 2D hydrodynamic modeling using the Surface-water Modeling System (SMS). The geometry of the model is formed from the mesh generated from the bed elevation based on the after-tsunami bathymetry survey. Two boundary conditions and one main input data are applied to this model: discharge data, tidal data and bed load data. Discharge data as an upstream boundary condition consists of minimum discharge, average discharge and maximum discharge. The downstream boundary is defined by a tidal curve predicted from 15 daily data. The bed load data is presented in the form of a gradation curve that describes the distribution of sediment grains. The simulation output indicates that sediment settles intensively downstream of the river mouth at high discharge and low tide. At low discharge and high tide, sediment tends to settle before the flow reaches the river mouth. Referring to the results of previous studies, the direction and velocity of sediment motion changed slightly after the tsunami. Changes in the direction and speed of movement are related to changes in bed morphology at the river mouth due to the 2018 Palu Tsunami.